Form 4 Bilingual Terminology Additional Mathematics - Tay, Choo Chuan (Penerbitan Daya Sdn. Bhd.(188832-X), 2013)
Form 4 Bilingual Terminology Additional Mathematics based on the latest KBSM Additional Mathematics Syllabus. All the terms are selected from the textbook and sentences related to the terms are bilingual